1902 N.J. Laws 294 - (:unkn) unknown (My University, 1902)
Ch. 107, 14, pt. 33: [T]o regulate or prohibit the manufacture, sale, storage or use of fireworks and the use of firearms in such city; to regulate or prohibit the manufacture, sale, storage, keeping, or conveying of gunpowder, kerosene, benzine [sic], gasoline, burning fluid, nitro-glycerine, dynamite, camphene, coal oil, spirit gas, petroleum and other dangerous or explosive materials, and the use of candles and lights in barns, stables and other buildings[.]
Keywords: DISCHARGE; TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER